Pengaruh Analisis Determinan Kinerja Keuangan BPR di Kota dan Kabupaten Tegal - Hapsari, Ira Maya; Susilawati, Agnes Dwita; Monalisa, Monalisa (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
Rural Banks (BPR) as one of the business actors in the banking world also have an important role in advancing the economy in Indonesia even though the scale of their business activities is not as large as commercial banks. The research objective is to determine the effect of BOPO on financial performance; determine the effect of LDIR on financial performance; determine the effect of NPL on financial performance; determine the effect of CAR on financial performance. This study uses a quantitative approach. The data analysis technique used is multiple linear regression analysis and significant test (t test, F test and coefficient of determination). The results of this study partially show that there is an influence of BOPO on BPR financial performance; there is an effect of LDIR on the financial performance of the BPR; there is no effect of NPL on the financial performance of BPRs in the City and Regency of Tegal; there is an influence of CAR on the financial performance of BPRs in the City and Regency of Tegal; there is no effect of the cash ratio on the financial performance of BPRs in the City and District of Tegal. Meanwhile, simultaneously, there is an effect of BOPO, LDIR, NPL, CAR, and cash ratio on the financial performance of BPRs in the City and District of Tegal.